POTENSI PENGELOLAAN DANA DESA SESUAI UU NOMOR 6 TAHUN 2014 TENTANG DESA DI PROVINSI KALIMANTANBARAT - Septiyarini, Dwi (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2017)
The purpose of this study is to provide a comprehensive understanding about the village funding management of which is covering the governing substance regulations, potential problems and solutions as well. Data and analysis is addresed based on result of Focus Group Discussions (FGD) involving related stakeholders. Likewise, literature review is arranged by studying the relevant laws and regulations of the village funding management. Meanwhile FGD is conducted to obtain primary data which is relevant to the issue. As the result of discussion, it can be known that there are some main issues in managing the village funding in West Kalimantan Province. From the results of the discussions, there are several aspects of the problem of fund management in the Province of West Kalimantan, which includes the human resources aspects, namely the existence of limited human resources competencies in the village either to the village, village apparatus or Village Consultative Agency (BPD), from the aspect of regulation The proportion of allocated village funds in the form of empowerment activities with allocations of 30% and development activities of 70% resulted in village heads and Village Consultative Bodies (BPD) having difficulties and doubts combining the use of village funds with ADD, in terms of APBDes funding, especially with respect to honorarium or village income, village apparatus and BPD sourced from village funds, District Government still has not followed up the Regulation of Minister of Village, Development of Disadvantaged Area and Transmigration of RI Number 1 Year 2015 About Guideline of Right of Rights Origins and Authorities And the socio-cultural aspects of different socio-cultural aspects and village developments throughout Indonesia leaving some major problems for observers, intellectuals and village fund managers, namely the suitability of the policy of use and allocation of village funds as regulated by the Village Law Socio-cultural conditions and village development respectively, the use of village funds to support sustainable village development and conflict management at the village level related to the use of village funds for development and empowerment.